2017
DOI: 10.18632/oncotarget.20310
|View full text |Cite
|
Sign up to set email alerts
|

GSTA1 diplotypes affect busulfan clearance and toxicity in children undergoing allogeneic hematopoietic stem cell transplantation: a multicenter study

Abstract: Busulfan (BU) dose adjustment following therapeutic drug monitoring contributes to better outcome of hematopoietic stem cell transplantation (HSCT). Further improvement could be achieved through genotype-guided BU dose adjustments. To investigate this aspect, polymorphism within glutathione S transferase genes were assessed. Particularly, promoter haplotypes of the glutathione S transferase A1 (GSTA1) were evaluated in vitro, with reporter gene assays and clinically, in a pediatric multi-center study (N =138) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
111
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(122 citation statements)
references
References 51 publications
10
111
1
Order By: Relevance
“…The search and selection process ultimately identified 19 studies for the meta‐analysis from the 142 articles obtained by the computerized search (Figure ). The characteristics of the studies are presented in Table . All the studies included in the analysis were assessed as being of high quality.…”
Section: Resultsmentioning
confidence: 99%
“…The search and selection process ultimately identified 19 studies for the meta‐analysis from the 142 articles obtained by the computerized search (Figure ). The characteristics of the studies are presented in Table . All the studies included in the analysis were assessed as being of high quality.…”
Section: Resultsmentioning
confidence: 99%
“…Despite its wide utilization, Bu presents a narrow therapeutic window. Higher rates of relapse and rejection occur among patients with a low Bu exposure, whereas over‐exposure correlates with transplant‐related toxicities such as acute graft versus host disease (aGVHD), sinusoidal obstruction syndrome (SOS) and death . Pharmacokinetic (PK) studies have demonstrated a high intra‐ and inter‐patient variability despite equivalent doses of Bu .…”
Section: Introductionmentioning
confidence: 98%
“…Functional polymorphisms in GST genes have been suggested to play a role interindividual variability in the PKs of busulfan . The influence of GST polymorphisms on busulfan PKs has also been suggested in Japanese children .…”
Section: Discussionmentioning
confidence: 99%
“…Ethnic variability should be recognized when generalizing the results of studies of busulfan PK. Interestingly, recent pharmacogenetic studies have shown that the effect of GSTA1 haplotype on busulfan clearance is associated with age . There is an obvious need for further research that combines PPK model‐based strategy with the findings on genetic polymorphisms to provide more effective busulfan TDM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation